2018
DOI: 10.1016/j.microc.2018.03.032
|View full text |Cite
|
Sign up to set email alerts
|

On the photoluminescence changes induced by ageing processes on zinc white paints

Abstract: Recent research is focusing on the study of interaction mechanisms between pigments and binder, as they are crucial for understanding paint ageing and conservation issues. In this work, we investigate these mechanisms and follow the changes induced by ageing on zinc white paint by employing Fourier Transform Infrared (FTIR) and Time-Resolved Photoluminescence (TRPL) spectroscopies. The two techniques, applied on thermally aged mock-up samples and on a 19 th oil painting, provide complementary information on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…These lifetime values are below those detected with spectrally resolved gated luminescence measurements in model samples and historical pastels but are on the same order of magnitude [17]. It has been suggested that trap state emissions may also decrease in lifetime following complexation of ZnO [23].…”
Section: Time Resolved Lifetime Imagingmentioning
confidence: 65%
See 2 more Smart Citations
“…These lifetime values are below those detected with spectrally resolved gated luminescence measurements in model samples and historical pastels but are on the same order of magnitude [17]. It has been suggested that trap state emissions may also decrease in lifetime following complexation of ZnO [23].…”
Section: Time Resolved Lifetime Imagingmentioning
confidence: 65%
“…The near band edge (NBE) transition at approximately 380 nm, together with blue luminescence (BL) between 400-500 nm and the green luminescence between 500-550 ascribed to trap states (TS) were observed in varying intensities in different paintings. Recent research on historical ZnO has reported the band gap and shallow trap states contribute to the NBE emission between 380-390 nm [17,23]. The NBE emissions reflect differences (Figure 2) in the concentration of shallow trap states that give rise to a red shift emission centred at 385 nm, a well-known phenomenon for semiconductors.…”
Section: Laser Induced Fluorescence (Lif) Spectroscopymentioning
confidence: 89%
See 1 more Smart Citation
“…This change can be attributed to the adsorption of carboxylate groups to the ZnO surface, which affects the electronic structure at ZnO surface and its luminescence properties (26). The changes in luminescence have been shown to be significant in the first days after mixing of pigment powders and oils, but stable in time once the paint film become dried (24) (25).Results of EPR analysis allow us to better explain this evolution in time of the photoluminescence signal as a consequence of the passivation of ZnO which reaches a steady-state after a few days after mixing.…”
Section: The Evolution Of the Amount Of Cumentioning
confidence: 99%
“…Some of these applications were described by J. J. Rorimer in the 1920s and 1930s and include the study of the surface alteration of marble statues, differentiating between original and reproduced dyed textiles, and spotting forged glass artifacts. , In paintings research, the photoluminescence behavior of many components such as binders, varnishes, and pigments has been thoroughly described in the literature. Photoluminescence spectroscopy and photography have shown their use as powerful tools for nondestructive material discrimination and as a method to reveal past cleaning and restoration interventions as well as the pigmentation throughout a work of art. More recent developments include the use of synchronous fluorescence and time-resolved photoluminescence (TRPL) spectroscopy. Both methods add a second dimension of analysis, which has been demonstrated to provide additional means to differentiate between painting components, and the latter has even shown potential as a probe for chemical interactions between pigment and binder. The same principles can be used to identify painting components on the microscale, revealing important information about the buildup of a work of art or the painting techniques used. …”
mentioning
confidence: 99%